2018
DOI: 10.1016/j.soard.2018.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy with Roux-en-Y reconstruction as a lean model of bariatric surgery

Abstract: BackgroundAltered enteroendocrine hormone responses are widely believed to underlie the beneficial effects of bariatric surgery in type 2 diabetes. While elevated postprandial glucagon-like peptide-1 (GLP-1) is considered one of the mediators, increased postprandial glucagon levels have recently been implicated.ObjectivesWe investigated hormonal responses in lean patients after prophylactic total gastrectomy (PTG), as a model of Roux-en-Y gastric bypass without the confounding effects of obesity or massive wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 13 publications
6
51
5
Order By: Relevance
“…However, where immunoassay data were available, the LC-MS peak area ratios for post-OGTT gut hormone levels in the gastrectomy group correlated well with immunoassay-derived concentrations. This indicates that the developed method is inherently quantitative, and is therefore applicable for the further development of fully quantitative studies using peptide standards and stable isotope labelled internal standards 10 . Arguably, our results suggest that nano LC-MS approaches are well suited for monitoring multiple peptides in parallel in small plasma samples.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, where immunoassay data were available, the LC-MS peak area ratios for post-OGTT gut hormone levels in the gastrectomy group correlated well with immunoassay-derived concentrations. This indicates that the developed method is inherently quantitative, and is therefore applicable for the further development of fully quantitative studies using peptide standards and stable isotope labelled internal standards 10 . Arguably, our results suggest that nano LC-MS approaches are well suited for monitoring multiple peptides in parallel in small plasma samples.…”
Section: Discussionmentioning
confidence: 96%
“…Experiments were performed on plasma samples from a published study, which have previously been analysed by immunoassay for a range of gut and pancreatic peptides 10 . The study was approved by the National Health Service Research Ethics Committee and conducted in accordance with the ethical standards of the Helsinki Declaration of 1975.…”
Section: Patients and Plasma Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pancreas, predominant expression of proconvertase 2 leads to preproglucagon processing to produce glucagon. Although some studies have reported an increase in postprandial glucagon after RYGB, a later study suggested that this work was confounded by the fact that RYGB causes large increases glicentin, another preproglucagon peptide that has increasing cross‐reactivity with standard glucagon enzyme‐linked immunosorbent assays with increasing plasma concentrations . Thus, more research is needed from independent groups utilising sensitive and specific assays to determine whether glucagon is increased with surgery or not.…”
Section: Mechanisms For Metabolic Successmentioning
confidence: 99%